Status Nutrisi Pasien Gagal Ginjal Kronik di Ruang Hemodialisa: Studi Deskriptif - Putri, Dian Agustina (Indonesian Academia Health Sciences Journal, 2020)
Objective: To find out the nutritional status of patients with chronic kidney Disease in the hemodyalisis room of Siti Khadijah Islamic Hospital of Palembang in 2019.Methode: This was a descriptive study design using Subjective Gloval Assasment (SGA) questionnaire with 90 respondents as samples.Result: Â The study result showed that most of male sex experienced chronic kidney failure as much as 54 (60%) respondents, and the nutritional status of patients with chronic reneal failure were at a mild stage (45, 50,0%) respondent.Conclusion: Most and of the nutritional status of patients was at a mild stage. And it is expected that the related health care workers could provide health education in fulfilling their nutritional status.